Simulasi Rambu Lalu Lintas AR Real-Time untuk Edukasi Interaktif Berbasis Gamifikasi - Eva Handriyantini; Bernard Dikson Gandawinata (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
Enhancing understanding and awareness of traffic safety is a critical challenge, particularly among younger generations. This study aims to develop a real-time Augmented Reality (AR)-based traffic sign simulation application integrated with gamification elements to improve user engagement and comprehension. The research employed a Research and Development (R&D) approach involving 30 respondents as application users. The development process included needs analysis, user interface design using a user-centered approach, implementation of markerless tracking technology, and integration of time-based challenges and virtual rewards as gamification elements. The testing results indicated a 30% improvement in post-test scores compared to pre-test scores, demonstrating the application's effectiveness in enhancing users' understanding of traffic signs. This application is not only relevant for formal education in schools but also holds potential as an innovative tool for traffic safety campaigns. The study supports the theory that the integration of AR and gamification can create engaging and effective learning experiences.